LOCALLY SMALL RIEMANN SUMS FUNGSI TERINTEGRAL HENSTOCK-DUNFORD PADA RUANG EUCLIDE R^n - Solikhin Solikhin (Universitas Pekalongan, 2013)
In this paper we study Henstock-Dunford integral on the Euclidean space R^n . We discuss some properties of the integrable. We shall define locally small Riemann sums (LSRS) and show that it is necessary and sufficient condition for function to be Henstock-Dunford integral on the Euclidean space R^n.